Human resource management : basics - Caers, Ralf, ....- (Antwerpen : Intersentia Educatief, 2019)
This handbook is an introduction to Human Resource Management, with a clear focus and without sidetracks. It discusses topics on recruitment and selection, provides answers to how socialisation and leadership can be applied to improve performance and helps to deal with dismissal of staff. The handbook is aimed at practitioners, with practical hints, examples and advice, that are always grounded by science. In today's organisations, HR occurs both within and outside of the HR-department. Just think about the daily leadership that is exerted by direct supervisors. This handbook therefore has two main goals. First, it provides its readers with the knowledge that can help them to become better employees and supervisors in organisations. Second, it provides the readers with a sufficiently strong background that enables them to study domains of HRM more in-depth. The handbook thus not only focuses on academic and professional bachelor students, but is open to everyone who works for an organisation.
Keywords: Human Resource Management